ANALISIS RISIKO HAZARD PADA PEMBUATAN KEMASAN KARDUS MENGGUNAKAN METODE HAZARD AND OPERABILITY STUDY DI UPTD. BALAI KEMASAN PRODUK DAERAH NTB - Eki Ruskartina; Nurul Hudaningsih; Iksan Adiasa; nurhayanti matuges (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2023)
MSMEs are said to be one of the economic activities in processing raw materials into finished materials that will provide added value. Micro, small and medium enterprises (MSMEs) must be able to find ways to grow their businesses. One of the ways is that MSME actors must pay attention to their product packaging. One of the companies that assisted in packaging was UPTD.Balai Regional Product Packaging, NTB. As well as in the manufacture of packaging requires accuracy to avoid work accidents. Therefore it is necessary to have recommendations for occupational accidents and safety (K3) to minimize hazards at work. In this study, the hazard and operability (HAZOP) method was used, which is a method for identifying and analyzing and providing recommendations for improvements in order to minimize work accidents so that the production process runs safely and smoothly